Wonder cat Kyuu-chan. 5 - Nitori, Sasami (Seven Seas Entertainment, 2022)
Hinata and Kyuu-chan eat ice cream, help a ghost enter a scaring contest, and spend their first night apart when Hinata has to go on a business trip. Kyuu-chan stays over at Mona-chan's house, and they have lots of fun together. Later, Hinata and Kyuu-chan go on a dessert tour, and Kyuu-chan meets another cat.